Influence Home Industry Kampoeng Batik Laweyan To Community Economy in the Laweyan Region of Surakarta - bagas ibnu s, Bagas ibnu saputro; Rohsulina, Pranichayudha (Journal of Geography Science and Education, 2023)
Surakarta is a city that is famous for its culture, industry, etc. Surakarta is also one of the districts in Central Java which has superior potential and functions in various sectors which can be utilized to improve welfare and increase people's income. One of them is in the industrial sector. A small and medium home industry that can increase people's income is the batik home industry. In Laweyan Batik Village, Laweyan District, Surakarta City, there are several batik home industries that can increase the income of the local community. The aim of this research is to analyze the influence of the batik home industry on increasing the income of the people of Kampung Batik Laweyan, Laweyan District, Surakarta City. This type of research is descriptive with a qualitative approach. Data collection techniques used include: 1). Informant observations, 2). Field survey, 3). In-depth interviews, 4). Documentation. The results of the research show that the batik home industry has an influence in increasing the income of the surrounding community. The efforts made by the owner of the batik home industry to increase the income of the surrounding community are by taking batik home industry workers from the surrounding community and increasing the batik production output and expanding the market and promoting it through the media. social services so that it will increase workers' income